Effect of platelet-rich plasma and platelet-rich fibrin matrix on healing of vertical meniscal tears in a rabbit model - Kurnaz, Recep (Acta Orthop Traumatol Turc, 2020)
OBJECTIVE: This study aimed to investigate the effect of platelet-rich plasma (PRP) and platelet-rich fibrin matrix (PRFM) on the healing of vertical medial meniscal tears in a rabbit model. METHODS: The study was conducted on 72 New Zealand mature rabbits aged more than 6 months. Rabbits were randomly assigned to six groups: control (C) group, meniscal repair (MR) group, PRP group, PRFM group, MR+PRP group, and MR+PRFM group, with 12 rabbits in each group. A 5-mm full-thickness vertical tear was created in the avascular zone of the medial meniscus corpus in the right knee of all rabbits. The respective treatment for each group was given to the meniscal tear in each rabbit. Histological evaluation of healing was performed 6 and 12 weeks after surgery. RESULTS: Defect filling and collagen formation remained low in the C group. However, in all other groups, there was no significant difference in the 6(th) week. In the 12(th) week, similar results as those obtained in the 6(th) week were obtained. In the C group, there was a difference in defect filling and cell type. This difference was that the defect filling and collagen formation remained low in the 12(th) week. No significant difference was observed between MR, MR + PRP and MR + PRFM groups. The MR group significantly differed from the other groups in the defect-filling rate and cell type; however, the use of PRP and PRFM did not provide an obvious benefit. CONCLUSION: The contradictory results obtained in previous studies emphasize the need for further research on the use of PRP in meniscal recovery and repair. We believe that if surgery is indicated, repair is absolutely necessary to improve the healing of the tissue in meniscal tears. Studies using human meniscal tissue for meniscal injury and those that evaluate clinical applications of PRP are warranted.